Adaptability in envelope energy retrofits through addition of intelligence features. (4th May 2019) - Capeluto, Guedi
ABSTRACT: A large proportion of the existing building stock worldwide needs renovation and upgrading that will help comply with new energy codes and reduce fuel consumption and greenhouse gas emissions. Improvements with minimal interference to inhabitants can be achieved by upgrading facades using elements that enhance energy efficiency and user comfort. Prefabricated energy retrofit systems have been suggested, but at present many lack adaptability to weather and usage conditions. This paper presents BRESAER, a retrofit system that provides adaptability through combination of passive strategies and intelligence features, which can be used in different climates and diverse building types. Energy performance was analysed for five types of European climates, results are shown for two climate types and three usages. A comparison was made of the presented system with a mostly passive retrofit system. Results show that in both climates, adaptability provides higher energy savings, complying with current definitions of very low-energy buildings.